Etheno DNA-base adducts from endogenous reactive species - Nair, Jagadeesan; Bartsch, Helmut (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 1999)
Promutagenic etheno (ε) adducts in DNA are generated through reactions of DNA bases with LPO products derived from endogenous sources or from exposure to several xenobiotics. The availability of sensitive methods has made it possible to detect three ε-adducts in vivo, namely εdA, εdC and N2,3-εdG. One probable endogenous source for the formation of these adducts arises from LPO products such as trans-4-hydroxy-2-nonenal (HNE), resulting in highly variable background ε-adduct levels in tissues from unexposed humans and rodents. The range of background levels of εdA×10−8dA detected inhuman tissues was <0.05 to 25 and in rodent tissues 0.02 to 10; the corresponding values for εdC×10−8dC were 0.01 to 11 and 0.03 to 24, respectively. Part of this variability may be associated with different dietary intake of antioxidants and/or ω-6 PUFAs which oxidize readily to form 4-hydroxyalkenals, as εdA and εdC levels in WBC-DNA of female volunteers on a high ω-6 PUFA diet were drastically elevated. Increased levels of etheno adducts were also found in the liver of cancer-prone patients suffering from hereditary metal storage diseases, i.e., Wilson's disease (WD) and primary hemochromatosis (PH) as well as in Long-Evans Cinnamon rats, an animal model for WD. Increased metal-induced oxidative stress and LPO-derived ε-adducts, along with other oxidative damage, may trigger this hereditary liver cancer. ε-Adducts could hence be explored as biomarkers (i) to ascertain the role of LPO mediated DNA damage in human cancers associated with oxidative stress imposed by certain lifestyle patterns, chronic infections and inflammations, and (ii) to verify the reduction of these ε-adducts by cancer chemopreventive agents. This article summarizes recent results on the formation, occurrence and possible role of ε-DNA adducts in carcinogenesis and mutagenesis.